(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1924)
The castle, which was the seat of the Durwards is located next to the medieval church. A historical background with documentary records is presented. Erected comparatively early in the thirteenth century, the Castle of Coull belongs to the older type of stone fortress characterised by a single envelope and the presence of a donjon. The excavation is described in detail with many plans and illustrations. All of the surviving components of the castle have been revealed. The ruins are now in very poor condition. A detailed report on the pottery and other artefacts is included.